Polyol mixture supplementation as a sweetener and/or feed additive in the diet of piglets - Näsi, Matti; Alaviuhkola, Timo (Agricultural and Food Science, 1981)
In a 2 X 2 factorial experiment the use of polyol mixture (sugar alcohols) in the diet of piglets was investigated by comparing it to sucrose as a sweetener or to growth promoter olaquindox. In the experiment 80 litters, eight or more piglets per litter, were allotted four dietary treatments: sucrose 4 %(1), sucrose 4% + olaquindox 50 mg/kg feed (2), polyol 8 %, 4 % DM (3) and polyol 8 % + olaquindox 50mg/kg feed (4). Creep feed was offered from one week’s age. The post weaning feeding period was from 5 to 7 weeks’ age. The litter size was 9.9 piglets on average. The mortality of piglets was 11.2%, 8.4 %, 8.8 % and 6.4 % in groups 1, 2, 3 and 4 during the experimental period 7—49 d. After weaning the groups receiving growth promoter grew significantly(P<0.01) better, 13.8 % and 24.0 % compared to the controls. Polyol and sucrose groups were equal. Feed consumption before weaning was small, 31 g/d, on average. After weaning there were no differences between groups in feed consumption. Relative feed conversion efficiences were 100,79, 90 and 81 for groups 1,2, 3 and 4. The growth promoter decreased the incidence of diarrhoea in piglets after weaning. By using polyol mixture as a sweetener sucrose could be substituted and the mortality of piglets was reduced. The use of growth promoter improved the performance of piglets.